Tracking mechanical Dauphiné twin evolution with applied stress in axial compression experiments on a low-grade metamorphic quartzite. (July 2018) - Minor, Alexander; Rybacki, Erik; Sintubin, Manuel; Vogel, Sven; Wenk, Hans-Rudolf
Abstract: The stress-dependent evolution of mechanical Dauphiné twinning has been investigated in axial compression experiments on a low-grade metamorphic quartzite, applying both time-of-flight neutron diffraction and electron backscatter diffraction. The data of the experimentally stressed quartzite samples were compared with those of the naturally deformed starting material to monitor Dauphiné twinning in relation to different experimental stress states. This comparison shows that in the experimental conditions of 500 °C temperature and 300 MPa confining pressure, Dauphiné twinning initiates below 145 MPa differential stress and saturates between 250 MPa and 460 MPa differential stress. A single grain orientation analysis (SGOA) has been developed based on the distinction of quartz grains free of Dauphiné twin boundaries (DTBs) and containing Dauphiné twin boundaries. Comparing pole figures and inverse pole figures of DTB-free grains of the starting material with those of the experimentally stressed samples shows a significantly different orientation distribution of the positive {10 1 ¯ 1} (r) and the negative {01 1 ¯ 1} (z) rhombs. In DTB-containing grains, the SGOA allows to distinguish between host and twin domains. Using DTB-free grains, the SGOA furthermore reveals a particular pattern, with one of the r rhomb maxima parallel to the axial compressive stress direction and a girdle with two r rhomb submaxima perpendicular to it. We believe that this relationship between the axial compressive stress direction and the rhomb orientation distribution shows the potential of the SGOA in the reconstruction of the paleostress state in naturally stressed quartz-bearing rocks. Highlights: Dauphiné twin evolution is monitored in axial compression experiments. Dauphiné twinning is easily induced by the axial compressive stress applied. A novel single grain orientation analysis is introduced. The single grain orientation analysis allows to distinguish twin and host domains. The single grain orientation analysis has the potential to determine paleostresses.